Research progresses of noble metal (Pt, Pd, and Ru)-based catalysts for catalytic decomposition of chlorine-containing volatile organic compounds - YANG Qin; XU Han; ZHAO Yaruo; TIAN Mingjiao; HE Chi* (能源环境保护)
Chlorine-containing volatile organic compounds (CVOCs) have become a focus and difficulty in the field of catalytic combustion of VOCs due to their extensive sources, high biological/environmental toxicity, and easy inactivation of catalyst via Cl poisoning. Catalytic decomposition is considered to be one of the most effective and feasible methods to reduce the emissions of CVOCs due to its significant advantages of low energy consumption, high efficiency and less secondary by-products. High performance catalysts are the key to this technology. At present, the CVOCs degradation catalysts are mainly composed of single or complex metal oxide supports (e.g., Al_2O_3, TiO_2, MgO, and CeO_2) and noble metal (e.g., Pt, Pd, and Ru) reactivity center. In the oxidation reaction of CVOCs, the noble metal is easy to interact with Cl at low temperature, covering/inerting the active site, and resulting in a decrease in the low-temperature activity of the catalyst. Commonly strategy to improve the catalytic performance of supported precious metal catalysts include metal additive doping, active center state optimization, carrier property regulation, reaction condition adjustment, etc. In this review, we briefly review the research progress of noble metal (Pt, Pd, and Ru)-based catalysts in the catalytic oxidation of CVOCs, including doping transition metals, changing the intrinsic properties of supports, and adjusting reaction conditions to improve catalytic efficiency and performance. In addition to this, the future perspectives toward the development of CVOC purification catalysts are put forward.